PERCERAIAN ATAS PERKAWINAN YANG DILANGSUNGKAN MENURUT HUKUM ADAT TIONGHOA DAN AKIBAT HUKUMNY - PATRICIA HALIM (PREMISE LAW JURNAL, 2015)
Many Indonesian citizens of Chinese descent conduct a marriage in accordance with Chinese traditional (adat) law and do not register their marriage according to the stipulation stated in Article 2 paragraph (2) of Law No.1/1974 on Marriage saying that the marriage is illegal until it is registered at the Service of Population Affairs. A divorce results in problems for the children and joint property. The data for this descriptive analytrical study with normative juridical approach were obtained from the regulations of legislation related to marriage and divorce through library research supported by the interviews with the Chinese public figures. The result of this study showed that legal consequence of the divorce of a marriage conducted in accordance with Chinese traditional (law) viewed from the marital property obtained during their marriage could be settled by deliberation and consensus or the stipulation stated in the Indonesian Civil Codes and through Article 37 of Law No.1/1974 on Marriage saying that the joint property can be distributed based on Adat and Religious Laws or other laws. But the baby who still needs special treatment from its mother will remain to be with its mother until the baby is six to 12 months old because the mother needs to breastfeed her baby up tp a certain period of time and a mother is regarded to have more patience in taking care of her baby compared with the father.   Keywords :       Divorce, Joint Property Distribution, Child Care, Responsibility of Providing a Living for the Child